Effective Governance: Helping Boards Acquire, Adapt and Apply Evidence to Improve Quality and Patient Safety - Kevin Barclay (Law & Governance, 2010)
[This article was originally published in Healthcare Quarterly 13(4).] They don't spend a lot of time treating patients. And they're seldom included on grand rounds. But health services boards of directors still have a significant role to play in quality and patient safety. Their responsibilities for quality go beyond those of boards in many other settings and so, therefore, does their need for specialized education and training. As Maura Davies, chief executive officer (CEO) of Saskatoon Health Region, has pointed out, "There is increasing awareness that health services boards cannot abdicate their responsibilities for ensuring quality and safety and need to take specific actions to address these duties" (Davies 2010: 37).